Stability analysis of real-time dynamic substructuring using delay differential equation models. - Wallace, M. I. (Earthquake engineering & structural dynamics.)
Real-time dynamic substructuring is an experimental technique for testing the dynamic behaviour of complex structures. It involves creating a hybrid model of the entire structure by combining an experimental test piece?the substructure?with a numerical model describing the remainder of the system. The technique is useful when it is impractical to experimentally test the entire structure or complete numerical modelling is insufficient. In this paper, we focus on the influence of delay in the system, which is generally due to the inherent dynamics of the transfer systems (actuators) used for structural testing. This naturally gives rise to a delay differential equation (DDE) model of the substructured system. With the case of a substructured system consisting of a single mass?spring oscillator we demonstrate how a DDE model can be used to understand the influence of the response delay of the actuator. Specifically, we describe a number of methods for identifying the critical time delay above which the system becomes unstable. Because of the low damping in many large structures a typical situation is that a substructuring test would operate in an unstable region if additional techniques were not implemented in practice. We demonstrate with an adaptive delay compensation technique that the substructured mass?spring oscillator system can be stabilized successfully in an experiment. The approach of DDE modelling also allows us to determine the dependence of the critical delay on the parameters of the delay compensation scheme. Using this approach we develop an over-compensation scheme that will help ensure stable experimental testing from initiation to steady state operation. This technique is particularly suited to stiff structures or those with very low natural damping as regularly encountered in structural engineering.